Longitudinal Associations Between Perceived Parent-Adolescent Attachment Relationship Quality and Generalized Anxiety Disorder Symptoms in Adolescence - van Eijck, Fenna E. A. M. (Springer US, 2012)
This longitudinal study examined the direction of effects between adolescents’ generalized anxiety disorder (GAD) symptoms and perceived parent-adolescent attachment relationship quality, as well as the moderating role of gender and age. 1,313 Dutch adolescents (48.5% boys) from two age cohorts of early (n = 923, M(age) = 12 at W1) and middle (n = 390, M(age) = 16 at W1) adolescents completed questionnaires regarding their attachment relationship to parents and GAD symptoms in four waves. Cross-lagged path analyses demonstrated that adolescents’ GAD symptoms and perceived father-adolescent attachment relationship quality bidirectionally negatively affected each other over time. For mothers, adolescents’ GAD symptoms negatively predicted perceived mother-adolescent attachment relationship quality over time. The within-wave correlated residuals between perceived attachment relationship quality with fathers and GAD symptoms were stronger for boys than for girls and stronger for the cohort of middle adolescents than for the cohort of early adolescents. This study demonstrates that both the parents’ and the adolescents’ gender as well as the adolescents’ age affects the relation between adolescents’ GAD symptoms and perceived parent-adolescent attachment relationship quality.